Business Reasoning for Rapid Productization in Small Enterprises - Hänninen, Kai; Muhos, Matti; Kinnunen, Tuomo; Haapasalo, Harri (Scientific Research, 2014)
In order to succeed, companies must offer quality products and services, ones that are in demand. Rapid productization (RP) is a concept originating from practical challenges expanding customer preferences. RP is a process of quickly supplementing a company’s product or service offering to meet unexpected customer preferences. The objective of this study is to describe how an RP exists in small enterprises and how the use of RP is reasonable. This case study opens the RP concept by clarification of business case objectives set to start RP, analysis of RP challenges and description of business reasoning used for RP in the case companies. Products offered to customers may be a result of cooperation among many companies, while the products are modular, consisting of interlinking elements. When these types of products are well managed, it can be easy to respond to changing customer requirements. This type of RP can be the livelihood of especially small- and medium-sized enterprises (SME). However, the capability of productizing rapidly provides a significant competitive edge also for larger players.
Keywords: Rapid Productization; Reasoning; Business Case; Decision Making; SMEs